Wajib Belajar 12 Tahun Di Desa Ampelan Kecamatan Wringin Kabupaten Bondowoso Tahun 2023 - Susilowati; Gufron, Emil; Balya, M. Danial; Rahayu, lilik Puja (Progresif : Media Publikasi Ilmiah, 2023)
The Ministry of Education and Culture's Strategic Plan for 2020-2024 is that 9 years of compulsory education will be completed, 12 years of compulsory education will increase and will prioritize poor families.Readiness of Ampelan Village, Wringin District, Bondowoso Regency to welcome the 12 year compulsory education program, it is necessary to know the description of the implementation of the 9 year compulsory education program first. The type of research used was quantitative descriptive with a population of all teenagers in Ampelan Village, Wringin District, Bondowoso Regency totaling 52 teenagers.Using total sampling with the inclusion criteria of children who had dropped out of junior high school, the sample size was 11 teenagers. Data was obtained through a questionnaire and research results will be presented in percentage form. The results of the study showed that 21% of children dropped out of secondary school in Ampelan Village, Wringin District.72% of the children who have dropped out of secondary schools come from families who work as agricultural laborers and have difficulty accessing secondary schools which are quite far away, having to go to othervilla